Advertising and Country of Origin as Key Success Factors for Creating Sustainable Brand Equity - Hanaysha, Jalal; Hilman, Haim (Journal of Asian Business Strategy, 2015)
Today’s markets have become highly competitive and challenging, therefore, a careful understanding of the key success factors that may help firms to sustain their brands is very important. In past literatures, it is evident that consumers prefer to purchase brands that provide them with unique values and differentiated features. However, this study focuses on advertising and country of origin effects as key success factors for building sustainable brand equity, because they were found to be important in influencing consumer behaviour. To explore our knowledge in this area, Malaysian automotive industry was selected. The data were collected from a total of 287 passenger cars owners through survey questionnaire at shopping malls in the northern region of Malaysia. The findings revealed that advertising and country of origin had significant positive effects on overall brand equity. Moreover, this study found that advertising and country of origin had significant positive effects on the dimensions of brand equity, namely; brand loyalty, brand image, brand awareness, and brand leadership. Based on the findings of this study, some implications have been highlighted to enhance our knowledge on the importance of the selected factors in building strong brand equity.